Eight new species of Moraea (Iridaceae) from southern Africa with range extensions and morphological notes in the genus - Goldblatt, Peter; Manning, J.C. (African Biodiversity & Conservation, 2013)
We describe eight new southern African species in the largely sub-Saharan African genus Moraea L., one from the winterdry Great Karoo and the others from the winter-rainfall zone of the southwest of the subcontinent. M. striata Goldblatt & J.C.Manning (subg. Visciramosae Goldblatt) from the southern foothills of the Great Swartberg Mtns has khaki-green flowers with reflexed tepal limbs streaked with dark lines. The acaulescent M. singularis Goldblatt & J.C.Manning (subg. Umbellatae Goldblatt & J.C.Manning) with terete leaf blades is restricted to the dry, interior foothills of the Kamiesberg in Northern Cape. M. filamentosa Goldblatt & J.C.Manning, subg. Acaules (Baker) Goldblatt & J.C.Manning, is described from the dry interior of Namaqualand in Northern Cape. The species is closely allied to the widespread M. falcifolia Klatt. In subg. Polyanthes (Goldblatt) Goldblatt & J.C.Manning, we describe M. thermarum Goldblatt & J.C.Manning (sect. Hexaglottis (Vent.) Goldblatt) from southwestern Namibia, allied to M. brevituba (Goldblatt) Goldblatt, and M. lazulina Goldblatt & J.C.Manning (sect. Pseudospicata Goldblatt & J.C.Manning) from the Little Karoo, until now confused with M. exiliflora Goldblatt but differing in its larger flowers with strongly reflexed tepals. The new M. petricola Goldblatt & J.C.Manning (subg. Vieusseuxia (D.Delaroche) Goldblatt), is restricted to higher elevations of the Pakhuis Mtns of northern Western Cape. Lastly, in subg. Homeria (Vent.) Goldblatt & J.C.Manning, we recognize M. doleritica Goldblatt & J.C.Manning with pale yellow flowers and anthers exceeding the style branches, restricted to dolerite outcrops in the Great Karoo, and M. eburnea Goldblatt & J.C.Manning from the northern foothills of the Klein Swartberg, which has a single, basal leaf and pale yellow flowers with filaments free distally. Moraea now has 222 species, including 203 in southern Africa, of which 200 are endemic to the region. In addition to describing new species, the paper brings to light range extensions of a further eight species: M. barnardii L.Bolus, M. elliotii Baker, M. exiliflora Goldblatt, M. falcifolia Goldblatt & J.C.Manning, M. fenestralis (Goldblatt & E.G.H.Oliver) Goldblatt, M. louisabolusiae Goldblatt, M. tulbaghensis L.Bolus and M. unguiculata Ker Gawl. Each of the species falls into one of the subgenera mentioned for the new species except M. fenestralis which belongs in subg. Galaxia.